A comparison of the life-history traits between diapause and direct development individuals in the cotton bollworm, Helicoverpa armigera - Chen, Chao (Oxford University Press, 2014)
In order to understand the differences of life-history traits between diapause and direct development individuals in the cotton bollworm, Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae), the development time, body size, growth rate, and adult longevity were investigated between the two populations, which were induced under 12:12 L:D and 16:8 L:D photoperiods, respectively, at 20, 22, and 25°C. The results indicated that the larval development time, pupal weight, adult weight, and growth rate were significantly different between diapause and direct developing individuals. The diapause developing individuals had a significantly higher pupal and adult weight and a longer larval time compared with direct developing individuals. However, the growth rate in diapause developing individuals was lower than that in the direct developing individuals. Analysis by GLM showed that larval time, pupal and adult weight, and growth rate were significantly influenced by both temperature and developmental pathway. The pupal and adult weights were greater in males than females in both developmental pathways, exhibiting sexual size dimorphism. The dimorphism in adult weight was more pronounced than in pupal weight because female pupae lost more weight at metamorphosis compared to male pupae. Protogyny was observed in both developmental pathways. However, the protogyny phenomenon was more pronounced at lower temperatures in direct developing individuals, whereas it was more pronounced in diapause developing individuals when they experienced higher temperatures in their larval stage and partial pupal period. The adult longevity of diapause developing individuals was significantly longer than that of direct developing individuals. The results reveal that the life-history strategy was different between diapause and direct developing individuals.